2023
DOI: 10.7554/elife.82676
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the catalytic activity of the tyrosine kinase Btk by the adaptor protein Grb2

Abstract: The Tec-family kinase Btk contains a lipid-binding Pleckstrin homology and Tec homology (PH-TH) module connected by a proline-rich linker to a ‘Src module’, an SH3-SH2-kinase unit also found in Src-family kinases and Abl. We showed previously that Btk is activated by PH-TH dimerization, which is triggered on membranes by the phosphatidyl inositol phosphate PIP3, or in solution by inositol hexakisphosphate (IP6) (Wang et al., 2015, https://doi.org/10.7554/eLife.06074). We now report that the ubiquitous adaptor … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…The extent to which the intrinsically disordered PRR region of BTK participates in additional, perhaps fuzzy, interactions with the BTK SH3–SH2–kinase region remains to be investigated. As well, interactions of the N-terminal region of BTK with both positive and negative regulators ( Liu et al, 2001 ; Nocka et al, 2023 ; Tsukada et al, 1994 ) may alter the dynamic characteristics observed here. It is also possible that the dynamic linker between the PHTH and SH3 domains of BTK may mediate phase separation ( Shelby et al, 2023 ) and clustering into signaling competent condensates.…”
Section: Discussionmentioning
confidence: 90%
“…The extent to which the intrinsically disordered PRR region of BTK participates in additional, perhaps fuzzy, interactions with the BTK SH3–SH2–kinase region remains to be investigated. As well, interactions of the N-terminal region of BTK with both positive and negative regulators ( Liu et al, 2001 ; Nocka et al, 2023 ; Tsukada et al, 1994 ) may alter the dynamic characteristics observed here. It is also possible that the dynamic linker between the PHTH and SH3 domains of BTK may mediate phase separation ( Shelby et al, 2023 ) and clustering into signaling competent condensates.…”
Section: Discussionmentioning
confidence: 90%
“…Peptides were extracted in 50% acetonitrile, 5% formic acid, 45% water, and dried with a vacuum centrifuge before mass spectrometric analysis. Samples of purified intact proteins and trypsin-digested proteins were submitted to the QB3/Chemistry Mass Spectrometry Facility at the University of California, Berkeley and analyzed using Synapt and Orbitrap instruments, as described elsewhere 46,47 .…”
Section: Methodsmentioning
confidence: 99%
“…We purified three variants of the BTK PH-TH module (residues 1-171): PH-TH WT , PH-TH E45K (the activating variant discussed above), and PH-TH Y42K (the mutation at the dimer interface that we suspect destabilizes the PH domain), all tagged with mNeon-Green at the C terminus. Bilayer adsorption was quantified by imaging using total internal reflection fluorescence (TIRF) microscopy, which can discriminate between protein in solution and on the bilayer, as described previously for the BTK PH-TH module [62] (Figure 8A).…”
Section: The Mutation E45k In the Btk Ph-th Module Promotes Membrane ...mentioning
confidence: 99%
“…80 µL of the SUV mixture was added to each well of an etched glass slide mounted onto a Sticky Slide VI 0.4 (Ibidi GMBH) and incubated for 30 min at room temperature. Each well was then washed with 1x hanks balanced salt solution (HBSS) under vacuum as described [62],…”
Section: Supported-lipid Bilayer Preparationmentioning
confidence: 99%
See 1 more Smart Citation